ANALISIS KUALITAS TES BAHASA ARAB BERBASIS HIGHER ORDER THINKING SKILL (HOTS) - Rahmi Nur Fauziah, Indah; Syihabudin, Syihabudin; Sopian, Asep (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
Educational evaluation is an important aspect, because with educational evaluation, it can be known to what extent the educational process has been achieved, it can also determine the next step regarding what is to be done. In the realm of evaluation, analyzing the quality of HOTS-based tests is still rarely to be done as was the case in Lembang MTs Al-Musyawarah. Arabic Language Teachers have not analyzed the quality of Arabic question items in the final examination (UAS). This research aims to determine the quality of hots-based instruments in final examination (UAS) questions of Arabic that are have not yet know. The type of research that used in this research is descriptive research, and 30 people as the sample of data. The results of this research show that the validity of the test be include high, and high reliability, 25 questions are not fit with the criteria for multiple choice writing, the level of difficulty not yet proporsional, distinguishing power enough, and effectiveness of deceivers are enough categories, and all questions include as Lots category with C1 numbers as much as 2 items, 2 items for C2, and C3 as much as 36 items of questions.